Sosialisasi Pencegahan Hipertensi dan Anemia Ibu Hamil - Liliek Pratiwi; Ito Wardin (Pusat Riset dan Inovasi Nasional, 2024)
West Java Province Health Profile in 2022, the cause of the highest maternal mortality rate is due to pregnancy hypertension at 29.64%, bleeding at 28.17% and other causes. This must be a concern for health workers and the community, because the health of pregnant women is a shared responsibility. The prevalence of pregnancy hypertension often occurs from five to ten out of one hundred pregnant women who have the potential to experience pregnancy complications, namely hypertension. Hypertension in pregnant women or gestational hypertension appears after 20 weeks of pregnancy, and will disappear after delivery. Factors that can increase the risk of pregnant women developing hypertension are obesity and diabetes mellitus. Pregnancy hypertension if there is protein in the urine then complications will lead to preeclampsia. Pregnant women must pay attention to early signs that lead to preeclampsia to maintain the health of mother and child. The highest cases of pregnant women with anemia were in West Java in 2019. Pregnant women who have complications of hypertension and anemia during pregnancy are at risk of giving birth to babies with low birth weight (LBW). AKI in pregnant and postpartum women, in West Java Province, occurs most often in the maternal age range of 20-35 years, there are also those above the age of 35 years with a percentage of 36%. One intervention strategy to reduce MMR is through pentahelix collaboration between the government, society, academics, professional organizations, the media and the business world, by continuing to emphasize health promotion through socialization on the prevention of hypertension and anemia in pregnant women.